"Self‐regulation, " a new facet of Hox genes' function. Issue 1 (2nd September 2013) - Sheth, Rushikesh; Bastida, Maria Félix; Kmita, Marie; Ros, Marian; Wellik, Deneen; Torres, Miguel; Ros, Marian
<x xml:space="preserve">Abstract</x> Background: Precise temporal and spatial expression of the clustered Hox genes is essential for patterning the developing embryo. Temporal activation of Hox genes was shown to be cluster‐autonomous. However, gene clustering appears dispensable for spatial colinear expression. Generally, a set of Hox genes expressed in a group of cells instructs these cells about their fate such that the differential expression of Hox genes results in morphological diversity. The spatial colinearity is considered to rely both on local and long‐range cis regulation. Results: Here, we report on the global deregulation of HoxA and HoxD expression patterns upon inactivation of a subset of HOXA and HOXD proteins. Conclusions: Our data suggest the existence of a "self‐regulation" mechanism, a process by which HOX proteins establish and/or maintain the spatial domains of the Hox gene family and we propose that the functionally dominant HOX proteins could contribute to generating the spatial parameters of Hox expression in a given tissue, i.e., HOX controlling the establishment of the ultimate HOX code. Developmental Dynamics 243:182–191, 2014. © 2013 Wiley Periodicals, Inc.